The Effect of Areca Nut Fiber and Pineapple Leaf Fibers and Polyester Composition on Mechanical Properties of Composite - Diva, Diva Akbar (Journal of Renewable Energy and Mechanics, 2024)
The Effect of Areca Nut Fiber and Pineapple Leaf Fibers and Polyester Composition on Mechanical Properties of Composite Diva Akbar*, Dody Yulianto Mechanical Engineering Study Program, Faculty of Engineering, Islamic University of Riau Jl. Kaharuddin Nasution Km 11 No.113 Perhentian Marpoyan, Pekanbaru Telp. 0761 – 674635 Fax. (0761) 674834 Email : divaakbar@student.uir.ac.id ABSTRACT Areca nut fiber and pineapple leaf fiber are types of fiber derived from natural fibers that are interesting to research as composite reinforcing fibers because currently they are very abundantly available. This research aims to make composite boards made from areca nut fiber and pineapple leaf fiber with polyester resin metrics for mechanical strength. This research varied different mixtures starting from areca nut fiber: pineapple leaf fiber: polyester resin, namely 20%: 30%: 50%, 25%: 25%: 50%, 30%: 20%: 50% using The hand lay up method was carried out three times in making composite board specimens. The highest bending strength results in sample one with a mixture of 20% areca nut fiber, 30% pineapple leaf fiber and 50% polyester resin were 52.60 Mpa, the impact value was 0.379 Joules/mm2. This is because there is the influence of the fiber and metric mixture which causes the elasticity modulus value to increase and because there is the influence of fiber density, where the smaller the density value the greater the mechanical strength, both bending strength and impact value. This phenomenon can be seen from macro observations, namely that composite boards experience fiber pull out with a fibrous brittle fracture type.